2018
DOI: 10.1080/09603123.2018.1497778
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of women’s sanitation practices in informal settlements in sub-Saharan Africa: a qualitative study in Mathare Valley, Kenya

Abstract: Despite evidence suggesting women are disproportionately affected by the lack of adequate and safe sanitation facilities around the world, there is limited information about the factors that influence women's ability to access and utilize sanitation, especially in sub-Saharan Africa. The purpose of this study was to explore factors influencing women's sanitation practices in informal settlements in Nairobi, Kenya. Information from 55 in-depth interviews conducted in 2016 with 55 women in Mathare Valley Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 33 publications
5
46
0
Order By: Relevance
“…Environmental factors. Research has shown that lack of access to water and sanitation may be associated with poor health outcomes for women in informal settlements [17,23,25,57,58]. Access to water and sanitation are also used as alternative or additional sociodemographic or wealth measures in these settlements [59,60].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental factors. Research has shown that lack of access to water and sanitation may be associated with poor health outcomes for women in informal settlements [17,23,25,57,58]. Access to water and sanitation are also used as alternative or additional sociodemographic or wealth measures in these settlements [59,60].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Gibbs, Govender, and Jewkes [19] found that 72% of women in informal settlements in South Africa reported moderate to high levels of depressive symptomology and 57.9% reported very high levels, compared to only 26.4% of women in a nationally-representative sample [20]. Some research suggests that, due to lack of access to adequate water, sanitation, and hygienic environments in informal settlements, female residents are also especially vulnerable to reproductive tract infections like vaginal and urinary tract infections (UTIs) [21][22][23][24][25]. One study, reporting on the prevalence of UTIs among women in informal settlements in Bangladesh, for example, found that 46% of women in the sample tested positive for a UTI [26].…”
Section: Women's Physical and Mental Health In Informal Settlementsmentioning
confidence: 99%
“…These roles and responsibilities put women in a critical position for establishing and maintaining safe and hygienic spaces within the household, ensuring that children form hygienic health- and sanitation-related habits, and helping to minimize illness from preventable diseases [16]. For example, findings from several studies suggest that women’s sanitation behaviors and their ability to access sanitation is linked to their children’s sanitation behaviors, especially for young children [18, 19]. Findings from a 2016 qualitative study suggest that one of the factors that influences women’s sanitation behaviors in informal settlements in Nairobi is the need to set an example and/or be a role model for their children’s sanitation practices [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, findings from several studies suggest that women’s sanitation behaviors and their ability to access sanitation is linked to their children’s sanitation behaviors, especially for young children [18, 19]. Findings from a 2016 qualitative study suggest that one of the factors that influences women’s sanitation behaviors in informal settlements in Nairobi is the need to set an example and/or be a role model for their children’s sanitation practices [19]. Other studies report that women with small children often take their children with them when they leave the home to access sanitation and/or collect water [20–22]—suggesting that the mother’s WASH-related behaviors may be linked to their children’s exposure to different environments and, consequently, their health [16, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in Mathare, carried out by the authors of this study, suggests that the majority of women living in these environments cannot, for a variety of reasons including lack of resources and/or time, fear of violence, health concerns, time of day, and building closures, access a toilet for all of their daily sanitation needs and, as a result, revert at least once in a 24 h period to using open defecation and/or plastic bags or buckets in their homes (which are then emptied into open drainages outside the home) to manage urination and/or defecation [18,33,34,35]. As more sanitation interventions are being introduced into settlements, women’s regular access to toilets is expanding.…”
Section: Discussionmentioning
confidence: 99%